2003
DOI: 10.1080/01587910303046
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Development and Evaluation of an Online Nursing Course

Abstract: Institutions of higher education acknowledge that online learning represents a growing segment of the modern learning environment, and most students have mastered basic computer skills. However, reluctance to engage in online learning remains among both faculty and students. This article presents a case study of three schools of nursing that collaboratively developed and implemented an online undergraduate-nursing course. The article discusses the challenges that were encountered by faculty and students. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…However, these barriers can impede learning if students do not have adequate time to spend with the course material. Success with online courses tends to require 6-10 hours a week, but many students underestimate the amount of time needed (Alexander et al, 2010;Chio, 2012). Additional research is needed to understand how to maximize learning for clinicians with limited availability in their schedule.…”
Section: ▪ Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, these barriers can impede learning if students do not have adequate time to spend with the course material. Success with online courses tends to require 6-10 hours a week, but many students underestimate the amount of time needed (Alexander et al, 2010;Chio, 2012). Additional research is needed to understand how to maximize learning for clinicians with limited availability in their schedule.…”
Section: ▪ Discussionmentioning
confidence: 96%
“…Time management and planning study time are important for students with multiple work and personal commitments. Thus, it may be helpful to provide students with a course schedule that outlines the time duration of each module, which would allow students to reserve specific time for course work and stay on track (Alexander et al, 2010). Attention also should be given to the length of the modules.…”
Section: Implications For Clinical Forensic Nursing Practicementioning
confidence: 99%
See 1 more Smart Citation
“…This seems contradictory, but it is consistent with the literature. Alexander et al (2003) reported that it took online students more time than students in traditional classrooms to complete course objectives. Allen et al (2002) conducted a meta-analysis using 23 studies and concluded that while the difference in levels of academic achievement between students involved in both traditional and distance education is insignificant, both groups tended to prefer traditional education over DE.…”
Section: Discussion Of Stage Four Evaluationmentioning
confidence: 99%
“…This seems contradictory, but it is consistent with the literature. Alexander et al (2003) reported that it took online students more time than students in traditional classrooms to complete course objectives. Allen et al (2002) conducted a meta-analysis using 23 studies and concluded that while the difference in levels of academic achievement between students involved in both…”
Section: Discussion Of Stage Four Evaluationmentioning
confidence: 99%